L’encenser de Lladó = The Lladó censer - Llongueras, Lourdes de Sanjosé i (Miscel·lània litúrgica catalana, 2023)
This article presents a study of the Lladó censer at the Episcopal Museum of Vic (MEV 3746). The dearth of historical documentation about this censer has led to a search for comparable pieces, such as silver and metal censers from the 6th-7th centuries with similar characteristics. Our study has allowed both the date of the Lladó censer’s creation and its possible manufacturing workshop to be determined.